ANALISIS UPAYA PENANGANAN PENGUNGSI URBAN DI DKI JAKARTA OLEH LEMBAGA SWADAYA MASYARAKAT DITINJAU MELALUI PENDEKATAN HUMANITARIANISME BARU - Alexandro Arthur Constantine (2023)
This research theoretically tries to explore the "nexus" between desecuritization and humanitarian action. The meeting point is hindered by the existence of discourse on the principles of humanitarianism in humanitarian action; between classic and new principles that contradict each other. Using qualitative approach by interviewing and observing refugees in DKI Jakarta and non-state actors which involved in handling asylum seekers and refugees in Indonesia found out that classic humanitarianism which was only carried out by providing humanitarian assistance failed to find common ground between the desecuritization process, where political activities was needed to de-influence the presence of refugees as a threat. On the contrary, the new humanitarianism principle emphasizes that political practices need to be carried out while providing humanitarian assistance so that humanitarian action can have an impact to support refugees while staying in Indonesia. This can be seen in the shift strategies of non-state actors in their efforts to desecuritize refugees through lobbying and advocacy efforts. Thus, the meeting point between desecuritization efforts and humanitarian action can meet through a new humanitarianism approach.